Isolation and Identification of Aspergillus niger Causes Otomycosis and Treatment by Phenolic Extract of Agaricus bisporus - Hussein , Sarah Ali; Al-Bahrani, Rusol Mohammed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
This study aimed to isolate and characterize fungus Aspergillus niger and treated by crude phenolic extract from Agaricus bisporus mushroom that contains a bioactive compound to treat fungi. Thirty samples were taken of suffered patients with otomycosis. Phenol extract was performed by HPLC technology, Molecular diagnosis of fungal isolation by PCR technique. Results show that the microscopic and culture examination on sabouraud dextrose agar medium showed that the fungal isolates A. niger had a percentage of (60%). The molecular diagnosis of fungal isolates using the polymerase chain reaction technique. HPLC showed being present of six biologically active substances in A. bisporus. Active substance (phenols) was extracted from the fungus A. bisporus, and the concentrations were prepared (6.25, 12.5, 25 mg/ml) and then tested against A. niger fungus using the assessment of antifungal activity, the antifungal activity of the extracts and the inhibition of fungal growth were calculated individually. The outcomes demonstrated that the extract's inhibitory activity Phenolic against A. niger a concentration of 6.25 mg/ml showed lowest inhibition activity, the diameter of the colony was (1.63 ± 0.18cm), while the concentration of 25 mg/ml was the maximum of inhibitory activity, the diameter of the colony, was (1.23±0.03 cm) compared to the control (8.67 ± 0.33 cm).